STRUCTURAL INTEGRITY MONITORING OF OFFSHORE STRUCTURES USING LIQUID PENETRANT TESTING - Efe Peter Iyomi; Isaque Moyses Guimaraes; Olutayo Opeyemi Ogunmilua; Edidiong Uboho (International Journal of Innovations in Engineering Research and Technology, 2021)
The offshore inspection is an integral part of the Oil and Gas industry, due to the structural failures, a huge sum of money and resources have been invested into ensuring that offshore structures are built according to procedures and specifications that will guaranty the integrity and overall reliability for the complete life of the structure which is usually between 25 – 30 years. The complex failure pattern of offshore structure’s means they will be prone to hazards; hence consistent inservice inspection techniques are required to monitor the structural integrity of these structures, and as a result, offshore inspections have developed over the past years with the introduction of Non-Destructive Examination (NDE) inspection techniques such as “LIQUID PENETRANT TESTING”.